Muslim Meranao Consumers on the Marketing Strategies for Halal Branded Food Products - Aldrich June Caraecle (Philippine Association of Institutions for Research, Inc., 2019)
Food consumption is very critical for Muslim consumers, as they have to consume halal products. For food companies to satisfy Muslim buyers and develop an effective marketing strategy, it is necessary for them to evaluate customer satisfaction. Thus, this study assessed the level of satisfaction of Muslim Meranao consumers toward the marketing strategies for halal branded food products. The study made use of descriptive survey research utilizing a researcher-made questionnaire, and the data was analyzed using Statistical Package for the Social Sciences (SPSS). Applying purposive sampling, a survey was conducted to a total of 120 Meranao customers, which comprised 40 Meranao fathers, 40 mothers, and 40 Meranao Ulama. The overall assessment of the three groups of respondents showed that Meranao consumers were not satisfied with the marketing strategies of food companies for their product, price, place, and promotion strategies, or the 4P's. The survey revealed that among the 4P's, promotion strategies got the highest mean score of 2.48, while price strategies had been found to have the lowest satisfaction with a mean of 2.26. The dissatisfaction felt by the consumers may signify problems with the existing strategies of the companies. The findings of the study will guide manufacturers in enhancing their marketing strategies to attain perfect compliance with halal business practices.